Experimental methods and instrumentation for chemical engineers - Patience, Gregory S. (Elsevier, 2013)
This book is a practical guide for research engineers and students, process engineers and consultants, and others in the chemical engineering field. It presents standard and emerging instrumentation technologies for measuring physical phenomena with a particular emphasis on chemical processes, including DOE and uncertainty theory.